2019
DOI: 10.20884/1.oa.2019.15.1.626
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of <i>Haslea ostrearia</i> Supernatant Adapted in Indonesia against Pathogenic Bacteria Relevant to Mariculture (In-Vitro Study)

Abstract: Haslea ostrearia has known as the only diatom which synthesizes a water-soluble blue pigment, marennine. It has some biological activities such as allelopathy, antioxidant, antibacterial, antiviral, and growth inhibitor. Marennine is available in two forms, intracellular which located in the apical of the cell and extracellular which released into the culture medium. This research aimed to test the bioactivity of Haslea ostrearia supernatant adapted in Indonesia as an antibacterial against pathogenic bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Marennine is responsible for the greening of oyster gills in Western Europe [ 4 , 5 , 6 , 7 ]. Marennine and marennine-like pigments also display several biological activities (e.g., antibacterial, antiviral, or antioxidant) qualifying them for putative use in aquaculture and biotechnology [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marennine is responsible for the greening of oyster gills in Western Europe [ 4 , 5 , 6 , 7 ]. Marennine and marennine-like pigments also display several biological activities (e.g., antibacterial, antiviral, or antioxidant) qualifying them for putative use in aquaculture and biotechnology [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality depends on the amount of concentration and the length of the test time (Dey and Harborne, 1991). Permatasari et al (2018), demonstrated that the H. ostrearia supernatant culture (hereafter called blue water, or BW) adapted in Indonesia can inhibit the pathogenic bacteria that are often found in aquaculture activities such as Vibrio harveyi and Staphylococcus aureus. This result confirmed that the semi-purified extracellular marennine can be advantageous in aquaculture due to its inhibition of the growth of pathogenic organisms.…”
Section: Introductionmentioning
confidence: 99%